Perbandingan Kadar Air dan NaCl Buah Nenas dan Keripik Nenas - Azlaini Yus Nasution; Nuraisyah Nuraisyah (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Pineapple (Ananas comosus L.) is a tropical fruit that is widely grown in the village of Kualu Nanas, Kampar, Riau. Pineapple chips are foods made from ripe pineapple flesh, cut or sliced ​​and fried using oil in a vacuum. This study aims to obtain organoleptic test results and water content and NaCl content in pineapple fruit and pineapple chips. The method of determining the water content is gravimetric while the NaCl content uses the argentometric titration method. The organoleptic test on pineapple chips complied with the requirements of SNI 01-4304-1996, namely characteristic odor, sweet-sour taste, normal color, crunchy texture, while the integrity of pineapple chips was only 80%. The average water content of pineapple is 88.68%, while the average pineapple chips is 3.88% and this fulfills the requirements of SNI 01-4304-1996. The average NaCl level in pineapple is 0.0481%, and in pineapple chips the average NaCl level is 0.9359%.